Blueprint for clinical N-of-1 strategies with off-label precision treatments in monogenic epilepsies - Victoria M. Defelippe; Eva H. Brilstra; Willem M. Otte; Ghislaine J. M. W. van Thiel; Helen J. Cross; Finbar O’Callaghan; Valentina De Giorgis; Emilio Perucca; Kees P. J. Braun; Floor E. Jansen (Orphanet Journal of Rare Diseases)
Abstract Precision treatments for monogenic epilepsies, i.e. treatments that can at least partially reverse the biochemical consequences of a pathogenic gene variant, have been gradually emerging over the years. To date, however, information on the efficacy of these treatments is mostly based on case-reports and retrospective studies. As a result, utilisation of precision treatments often lack consistency and a pre-defined outcome monitoring plan. N-of-1 strategies in clinical care are pre-defined, individually tailored, repeated challenge-withdrawal therapeutic trials designed to assess the value of a treatment of interest for an individual. Despite their potential to improve clinical decision-making, N-of-1 strategies have been hampered by limited guidance on their implementation and lack of consensus on oversight procedures. To improve treatment selection for rare monogenic epilepsies, the PINPOINT initiative (Precision Treatments In MoNogenic EPilepsies: Observational Registry And N-of-1 Trial Recommendations) was set up as a collaborative effort within the European Reference Network for Rare and Complex Epilepsies. PINPOINT aims to develop recommendations for the design of N-of-1 strategies with off-label precision treatments for monogenic epilepsies. Using available N-of-1 trial manuals, different components of N-of-1 design were tailored to the context of epilepsy and oversight procedures were outlined. These efforts resulted in this guidance document—or blueprint for N-of-1 strategies for monogenic epilepsies in clinical care. This blueprint defines the characteristics of treatments and patients that would be suitable for N-of-1 strategies. Key principles for outcome measure selection, period duration and statistical analysis are defined. Consideration is given to interim assessment rules, which establish whether proceeding onto an additional treatment cycle is likely to provide significant advantages. Procedures for ethical oversight are proposed. This blueprint for N-of-1 strategies can be used as a basis for master protocols to optimise individualised clinical care in a standardised and consistent manner. We are confident that this document will provide physicians with the building blocks needed to elevate precision treatments for rare monogenic epilepsies out of their current landscape of inadequate evidence.